Synthesis of modified hydrocalumite : a novel katoite/portlandite precursor method - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2016)
Dissertation (MEng)--University of Pretoria, 2016.